2003
DOI: 10.2307/3558984
|View full text |Cite
|
Sign up to set email alerts
|

WIC Eligibility and Participation

Abstract: This study examines WIC eligibility and participation using the Current Population Survey (CPS) and the Survey of Income and Program Participation (SIPP). Comparisons of these sources to administrative totals suggest that participation is significantly undercounted in the CPS and in SIPP. However, the characteristics of families reported to receive WIC in the CPS and SIPP are similar to the administratively reported characteristics of WIC recipients nationally, which suggests that the undercount may be mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
163
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(169 citation statements)
references
References 12 publications
6
163
0
Order By: Relevance
“…For example, Bitler, Currie, and Scholz (2002) Cody and Castner (1999). The average calculated FSP benefit for households with an elderly person from the HRS is $81, which is similar to the average benefit of $63 reported in the QC data for the same population.…”
Section: Benchmarking the Hrs Reports Of Fsp Participationmentioning
confidence: 99%
“…For example, Bitler, Currie, and Scholz (2002) Cody and Castner (1999). The average calculated FSP benefit for households with an elderly person from the HRS is $81, which is similar to the average benefit of $63 reported in the QC data for the same population.…”
Section: Benchmarking the Hrs Reports Of Fsp Participationmentioning
confidence: 99%
“…Among very young children, Marianne Bitler and colleagues found that, accounting for characteristics associated with enrolling in the program, infants and toddlers who participated in WIC had healthier weight for age. 28 Federally subsidized school meals have the potential to improve children's nutrition, because the meals served must adhere to nutritional requirements. For example, one study that estimated effects of both the Supplemental Nutrition Assistance Program and the National School Lunch Program found that for girls living in "food-insecure" households (households without access to adequate food), participation in the programs reduced weight gain.…”
mentioning
confidence: 99%
“…Bhargava and Manoli (2015), Currie and Grogger (2001), Krueger (1990), Bitler et al (2003) and Brien and Swann (1999)). These increased application costs include requiring more frequent visits to the welfare office, reduced re-certification intervals or requiring extensive income documentation.…”
mentioning
confidence: 99%